GOOGLE SITES-BASED LEARNING MEDIA ON EARTHQUAKE AND TSUNAMI DISASTER MITIGATION: STUDENTS' PREPAREDNESS IN MIDDLE SCHOOL - Novianti, Iin; Nadjamuddin, Lukman; Listiqowati, Ika; Widyastuti, Widyastuti; Latief, Juraid Abdul; Hanis, Hasdin (Universitas Labuhanbatu, 2025)
Purpose – This study aims to develop a Google Sites-based disaster mitigation learning media to examine the preparedness of students toward earthquake and tsunami disasters at SMPN 1 Balaesang Tanjung.Methodology – This study employed a Research and Development design using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research involved a total sampling of 32 eighth-grade students at SMPN 1 Balaesang Tanjung. The intervention was carried out by developing a Google Sites-based learning media focused on disaster mitigation for earthquakes and tsunamis. Data were collected using Likert-scale questionnaires to assess three leading indicators: content quality, visual appearance, and benefits. The data were then analyzed using descriptive quantitative techniques to determine the effectiveness of the developed media.Findings – The Google Sites-based learning media on earthquake and tsunami disaster mitigation developed in this study proved to be highly effective in supporting disaster mitigation education. It achieved an effectiveness score of 87.5% for content quality (very effective), 84.4% for visual appearance (effective), and 86% for benefits (very effective), with an overall average score of 86%, indicating a classification as very effective.Contribution – This study presents an innovative web-based learning medium that integrates disaster mitigation content specifically designed for schools in high-risk areas, utilizing Google Sites for disaster preparedness.